OPTIMAL CONDITION FOR MULTIPLEX POLYMERASE CHAIN REACTION (PCR) IN DETECTING ASCARIS LUMBRICOIDES, TRICHURIS TRICHIURA, AND NECATOR AMERICANUS IN PRESERVED STOOL - Christiane Marlene Sooai; Elsa Herdiana M; Supargiyono Supargiyono (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Multiplex PCR examination is one of the molecular examination methodologies applied to detect soil-transmitted helminth (STH) infection. Optimization of the multiplex PCR method is a complex process, but it is necessary to obtain both a correct detection process and a satisfactory DNA product. Objective: To determine whether multiplex PCR can be optimized to diagnose STH from Indonesian isolates, and to find the optimal method for detection of A. lumbricoides, T. trichiura, and N. americanus infections in stool that have been stored for 3 years. Methods: A total of 15 samples were examined, and these samples were previously examined by using a microscopic method, then continued with optimization steps. Result: The optimal PCR mixture used primers targeting COI gene for A. lumbricoides, 18S rDNA for T. trichiura and ITS1 for N. americanus, 15 µl of Go Taq Green Master Mix, 5 µl of the 3 pairs of primers, 5 µl of DNA template and 4 µl of DdH2O, and the condition was 30 minutes of 950C denaturation, 30 second of 530C annealing and 1 minute of 720C extension, repeated for 35 cycles. Conclusion: Multiplex PCR can be optimized for STH detection from Indonesian isolates. The successful detection using the multiplex PCR method was influenced by sample preparation prior to DNA isolation, which includes several steps i.e. homogenization of samples using bead beaters and passing samples on liquid nitrogen rapidly.